THE EFFECTS OF TAX AVOIDANCE, BLOCKHOLDER OWNERSHIP, INDEPENDENT COMMISSIONER AND AUDIT COMMITTEE ON FIRM VALUE - Sitardja, Meco (Indonesian Journal of Accounting and Governance, 2017)
The objective (s) of this research wasanalyzing whether tax avoidance, blockholder ownership,independent commissioner, and audit committee have any influence to firm value. Thisresearchusessecondary data andpurposive samplingconsisting of 72 listed companiesin themanufacturing sector in Indonesia. The data was analysed in SPSS using multiple regression. Theresultshows that tax avoidance, institutional ownership, and independent commissionerdon’t influencesignificantly on firm value. Then, audit committee has positiveimpact on firm value.Simultaneously, taxavoidance, blockholder ownership, independent commissioner, and audit committee have significantimpact on firm value.